Perancangan Shaking Rig Simulator Irregularities Sarana dan Prasarana Kereta Api - Paresya Arva Seta; Agustinus Winarno; Budi Basuki; Ignatius Aris Hendaryanto (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
The train is one of the main modes of transportation used in various countries in the world, including Indonesia. The existence of an efficient railway network can support the mobility of people and goods. The safety and comfort of train travel is highly dependent on the condition of the railway facilities and infrastructure. The condition of facilities and infrastructure that meet standards will make the journey smoother and reduce the risk of accidents. With human mobility, the development of public transportation using trains in Indonesia also continues to increase. Damage to train tracks can cause disruption to comfort and endanger safety caused by excessive vibration during train travel, so regular maintenance and repair of the rails is required using a system called the Intelligent Railway Vibration Monitoring System (IRV-MS). The IRV-MS system still needs to be tested because the resulting vibration readings still require validation. The design of this shaking rig simulator is expected to be a solution in terms of vibration testing. This shaking rig can move in a vertical or horizontal linear direction with a linear motor as a driver and produce oscillatory movements. The design of this shaking rig simulator tool uses Solidworks software with 500 mm x 423 mm x 380 mm of dimension and later vibration animation will be simulated in the motion study feature in the software with input parameters of 3-10 Hz with a maximum stroke of 20 mm.